Assessment of the fracture properties of adhesively bonded joints submitted to fatigue loads using the Arcan fixture. Issue 3 (23rd November 2022) - Bernolin, C.; Stamoulis, G.; Bidaud, P.; Dagorn, N.; Albouy, W.; Thévenet, D.
Abstract: In the present study, the crack propagation behavior under cyclic loading of an epoxy‐based adhesive was investigated by the means of an Arcan device, in the mixed‐mode plane I+II. The strain energy release rate (SERR) was calculated through an inverse identification method using a Finite Element (FE) modeling. The evolution of the cracked surfaces revealed three main stages during the tests. It was found that under fatigue loading, the crack propagated at a value of SERR per cycle lower than the values of the critical SERR calculated under monotonic loads. The evolutions of the crack propagation rate against the SERR are also provided to highlight the effects of the mixed‐mode ratio on fatigue crack propagation. Highlights: The fatigue crack propagation in adhesively bonded assemblies was investigated using non standard Arcan tests A specimen geometry was proposed in order to stabilize the crack propagation. The effects of the mixed‐mode ratio on the crack propagation were analysed. A numerical methodology to compute the value of the SERR under fatigue loading was developed.